A review of sitagliptin with special emphasis on its use in moderate to severe renal impairment - Eligar VS; Bain SC (Dove Medical Press, 2013)
Vinay S Eligar,1 Stephen C Bain2 1University Hospital of Wales, Cardiff, UK; 2Singleton Hospital, Swansea University, Swansea, UK Abstract: Sitagliptin is the first dipeptidylpeptidase-4 inhibitor to be used in the management of type 2 diabetes. It is widely used as an add-on therapy to ongoing management or as monotherapy where it is deemed necessary. It has been found to be beneficial in improving β-cell function and glycemic control, and also is used in special circumstances like chronic kidney disease, with appropriate dose reductions. Overall, cardiovascular outcomes are no different from other oral hypoglycemic agents. In this review article we have summarized all the previous studies relevant to sitagliptin use in clinical practice and emphasized its use in various stages of chronic kidney disease. Keywords: sitagliptin, CKD, chronic kidney disease, renal impairment